2019
DOI: 10.3390/e22010010
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Load and Price Forecasting Using Jaya-Long Short Term Memory (JLSTM) in Smart Grids

Abstract: In the smart grid (SG) environment, consumers are enabled to alter electricity consumption patterns in response to electricity prices and incentives. This results in prices that may differ from the initial price pattern. Electricity price and demand forecasting play a vital role in the reliability and sustainability of SG. Forecasting using big data has become a new hot research topic as a massive amount of data is being generated and stored in the SG environment. Electricity users, having advanced knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Zhou et al [23] coupled LSTM and ensemble empirical mode decomposition (EEMD) to forecasting electricity markets of Pennsylvania, New Jersey, and Maryland. Khalid et al [24] proposed an optimized deep neural network framework to conduct electricity price forecasting based on the Jaya optimizer and LSTM approach. The main drawback of this proposed approach is related to the lack of the use of exogenous variables and use of decomposition approaches to cap the data variability.…”
Section: Related Workmentioning
confidence: 99%
“…Zhou et al [23] coupled LSTM and ensemble empirical mode decomposition (EEMD) to forecasting electricity markets of Pennsylvania, New Jersey, and Maryland. Khalid et al [24] proposed an optimized deep neural network framework to conduct electricity price forecasting based on the Jaya optimizer and LSTM approach. The main drawback of this proposed approach is related to the lack of the use of exogenous variables and use of decomposition approaches to cap the data variability.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of the proposed deep CNN is evaluated using the mean absolute percentage error (MAPE), and root mean square error (RMSE) [71]. The smaller value of the error provides better forecasting accuracy.…”
Section: B Evaluation Of the Proposed Deep Cnn With The Existing Modelsmentioning
confidence: 99%
“…A building's power demand is strongly related to the activities carried out inside it and the weather conditions [36]. Although the power curve for building's energy demand is more or less the same throughout a year, it is also affected by other phenomena such as the season and time of day [37]. Therefore, it was concluded that season and time in 15-min intervals should be analysed as possible input parameters.…”
Section: Power Demand Evolutionmentioning
confidence: 99%